2014
DOI: 10.1051/alr/2014007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary water content on European sea bass (Dicentrarchus labrax) growth and disease resistance

Abstract: -The effect of dietary water content on Dicentrarchus labrax growth parameters and resistance to Vibrio anguillarum infection was investigated using commercial pellets with identical energy contents and different moisture levels. The first experiment hypothesis was that moisturizing pelleted ration can have an impact on Dicentrarchus labrax growth performance by the osmoregulation energy cost reduction. In a second time, the experiment explores the effect of water addition in pellets on the fish resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Fish were acclimatized with a commercial diet for one month, when all groups showed a feeding behavior consistent with the stocking density and development stage [39,41]. Three tanks were used for each experimental formulation (VEG-control, SPI, YEA, INS, and PAP), and one tank was used for the commercial condition COM.…”
Section: Fish and Experimental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish were acclimatized with a commercial diet for one month, when all groups showed a feeding behavior consistent with the stocking density and development stage [39,41]. Three tanks were used for each experimental formulation (VEG-control, SPI, YEA, INS, and PAP), and one tank was used for the commercial condition COM.…”
Section: Fish and Experimental Conditionsmentioning
confidence: 99%
“…The COM tank was not considered for statistical analysis of growth performance but used as an informative growth curve baseline. In classical fish nutrition experiments, the diet is evaluated until the fish body weight has tripled [41]. This single COM tank was our biological indicator to decide at which time to stop the experiment and the source of control fish gut samples for analyzing bacterial biodiversity.…”
Section: Fish and Experimental Conditionsmentioning
confidence: 99%
“…Several pathogens can put the life of cultured seabass in jeopardy with consequent detrimental impacts on growth, fecundity and productivity [2]. Photobacteriosis caused by the halophilic bacterium Photobacterium damselae subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The modern feed form for aquaculture fish is dried pellets with less than 10% moisture. However, a study has shown that feeding fish using a moist formulation, such as algae or aquatic worms, with a water content around that of the natural prey profile in oceans, did not affect fish growth parameters and in fact increased resistance and immune protection (Przybyla et al, 2014). Thus, photosynthetic or invertebrate aquatic organisms produced in a Moon or Mars greenhouse could be fed directly to aquaculture fish with no transformation process.…”
Section: Feeding Fish In Space: Integrated Multi-trophic Aquaculturementioning
confidence: 99%